The labor market costs of conflict: closures, foreign workers, and Palestinian employment and earnings - Sami H. Miaari; Robert M. Sauer (Institute for the Study of Labor (IZA), 2006)
In this paper, we measure the implications of the Israeli-Palestinian conflict for Palestinian employment and earnings. We quantify the conflict by the frequency of temporary closures of the West Bank and Gaza Strip and the number of overseas foreign workers in the Israeli labor market. Data on Palestinian employment and earnings are taken from the Palestinian Labor Force Survey (PLFS) of the Palestinian Central Bureau of Statistics. The PLFS micro level panel data are combined with quarterly time series data on the number of foreign workers in Israel, the number of foreign worker permits issued by the Israeli government, and the frequency of temporary closures of the West Bank and Gaza Strip, between the years 1999 and 2004. Fixed-effects estimates which exploit the number of foreign worker permits issued by the Israeli government as an instrument for the number of foreign workers, yield large and statistically significant negative effects of the Israeli-Palestinian conflict on Palestinian employment rates in Israel and mean monthly earnings, regardless of work location (Israel or West Bank and Gaza Strip). Closures also significantly reduce Palestinian employment rates in Israel and mean monthly earnings. The impact of foreign workers is relatively stronger than the impact of closures because foreign workers are long-run substitutes for Palestinians in the Israeli labor market while closures represent only a transitory, short-run restriction on Palestinian labor supply. However, the impact of foreign workers also reflects a permanent effect of closures.
Keywords: 330